Analisis Pengaruh Risiko Kredit, Likuiditas, dan Efisiensi Manajemen Terhadap Profitabilitas Bank BUMN, Serta Perbandingan Kinerja Keuangan Bank Bumn dengan Bank Swasta : (Studi Kasus Tahun 2013 –2022) - Siskadea Sawitri Nasution; Gia Kardina Prima (Universitas 45 Surabaya, 2024)
This research aims to identify the causes of profitability fluctuations in state-owned banks, which significantly impact Indonesia's economic growth. Understanding these risks is crucial to maintaining the stability and competitiveness of state-owned banks against private banks. This identify the influence of non-performing loans (NPL), loan-to-deposit ratio (LDR), and operational costs on operating income (BOPO) on return on assets (ROA) of state-owned banks from 2013-2022. It also compares ROA, NPL, LDR, and BOPO between state-owned and private banks. The study uses a quantitative approach, with multiple linear regression for influence analysis. Then, sample t-tests and Mann-Whitney tests for comparison analysis. It analyzes secondary data from 40 annual financial ratio observations, involving 4 state-owned and 4 private banks. Findings show in state-owned banks that NPL significant negatively impact ROA, LDR has no effect to ROA, and BOPO significant negatively impacts ROA. Together, NPL, LDR, and BOPO significantly influence ROA. Comparatively, there is no difference in ROA, LDR, and BOPO between state-owned and private banks, but there are differences in NPL.